ROLE OF SPORT PSYCHOLOGY IN ENHANCEMENT OF SPORT PERFORMANCE - Kahalekar, Jaideep Govindrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sport psychology plays a crucial role in optimizing athletic performance by addressing mental factors that influence physical outcomes. This paper reviews the historical development, key interventions, and empirical evidence from meta-analyses demonstrating how psychological skills training (PST), mindfulness, imagery, and other techniques enhance performance. Drawing on systematic reviews and meta-studies, it highlights moderate to large effect sizes for positive psychological constructs while identifying challenges like study quality and the need for robust methodologies. The discussion underscores the integration of sport psychology in training regimens to achieve peak performance and well-being.